Family income and participation in post-secondary education - Miles Corak; Garth Lipps; John Zhao (Institute for the Study of Labor (IZA), 2004)
The relationship between family income and post-secondary participation is studied in order to determine the extent to which higher education in Canada has increasingly become the domain of students from well-to-do families. An analysis of two separate data sets suggests that individuals from higher income families are much more likely to attend university, but this has been a long-standing tendency and the participation gap between students from the highest and lowest income families has in fact narrowed. The relationship between family income and post-secondary participation did become stronger during the early to mid 1990s, but weakened thereafter. This pattern reflects the fact that policy changes increasing the maximum amount of a student loan as well as increases in other forms of support occurred only after tuition fees had already started increasing.
Keywords: J62; I2; 330; university; educational finance; intergenerational mobility; Bildungsverhalten; Studium; Studienfinanzierung; Haushaltseinkommen; Familiensoziologie; Schätzung; Kanada